A study on activation of polyethylene glycol and its characterization by infrared spectroscopy and thin layer chromatography - Bashyal, R. (Journal of Agriculture and Forestry University, 2022)
Polyethylene Glycol (PEG) is the most popular polymeric material used for alteration and control of biodistribution. PEG may increase the lifetime of “drug carrier” assembly which helps in administering lower concentration of the “drug carrier” composite. It has been used widely for the modification of carriers used in therapeutics because PEG offers a shielding characters that avoids rapid renal clearance from the body. This study was carried out at Dolphin Institute of Biomedical and Natural Sciences, Dehradun and Indian Institute of Technology (IIT), Roorkee, India during May-July 2005. Activation of PEG of different molecular weight (400 Da, 4000 Da, 8000 Da and 20,000 Da) was done using dry benzene, Triethylamine, Ethylene dichloride and 4-nitrophenyl chloroformate. Reaction mixture was monitored on TLC using EDC: Methanol (7:3). Then reaction mixture was portioned between EDC & water. The lower fraction in separating funnel of EDC was collected & concentrated on rota evaporator to get activated PEG. From the above reaction and structure it was clear that 4-Nitrophenyl Chloroformate contains two highly electronegative groups i.e. NO2 and Cl. These two groups interact with each other resulting in neutralization of polarity. It then acts as non-polar molecule and shows high affinity for mobile phase (methanol & EDC). Therefore, 4-Nitrophenylchloroformate has the highest mobility and PEG has lowest mobility. From IR Spectroscopy it was found that the peak of Hydroxyl group- (OH) of PEG was at 3400- 3450cm-1. The peak of C-Cl bond was found at 746 cm-1. But after the reaction between PEG and 4-Nitrophenyl Chloroformate the- OH peak was found not so deep as in PEG. The peak was somewhat short and broad.